2001
DOI: 10.1089/109264201317054555
|View full text |Cite
|
Sign up to set email alerts
|

Pericholecystic Adhesions in Single v Multiple Gallstones and Their Consequences for Laparoscopic Cholecystectomy

Abstract: Dense adhesions in the porta hepatis are significantly more common in patients with single stones and are the most common reason for open conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…According to our findings multiple stones were mostly present in patients of gallstones, which were in accordance with studies in the past [4,18]. Gallstones are of three varieties; most commonly they are composed of cholesterol followed by pigment and mixed stones [4].…”
Section: Discussionsupporting
confidence: 91%
“…According to our findings multiple stones were mostly present in patients of gallstones, which were in accordance with studies in the past [4,18]. Gallstones are of three varieties; most commonly they are composed of cholesterol followed by pigment and mixed stones [4].…”
Section: Discussionsupporting
confidence: 91%
“…[16][17][18][19] In our study, only 23 cases had suffered from acute attack and out of this only 03(13.04%) were converted. This rate of conversion in our study may be attributed to the low incidence of acute cases and all these acute cases were operated within IST 72 hours of presentation as within this period there is edema in the tissue planes, which magnify the structures and help in dissection.…”
Section: Resultsmentioning
confidence: 96%
“…They reported a conversion rate of 50% out of 78 patients with previous upper abdominal surgery. Correlation of chance of conversion with regard to stone size has been studied in various series as well 13,14 . While Saber et al 14 reported stone >1cm size to be a predictor of difficult LC, Verma et al 13 large stone size in cases of single gall stones correlated with a higher conversion rate.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation of chance of conversion with regard to stone size has been studied in various series as well 13,14 . While Saber et al 14 reported stone >1cm size to be a predictor of difficult LC, Verma et al 13 large stone size in cases of single gall stones correlated with a higher conversion rate. In the present study we too observed a significantly higher rate of conversion with stone size >1.5cm.…”
Section: Discussionmentioning
confidence: 99%